Microbiome, Immunosenescence, and Chronic Kidney Disease - Stavropoulou, Elisavet; Kantartzi, Konstantia; Tsigalou, Christina; Aftzoglou, Konstantina; Voidarou, Chrysa; Konstantinidis, Theocharis; Chifiriuc, Mariana Carmen; Thodis, Elias; Bezirtzoglou, Eugenia (Frontiers in Medicine, 2021)
Gut microbiome is stated as an important predictive tool for perceiving characteristic shifts in disease states. Multiple renal diseases and pathologies seem to be associated with gut dysbiosis which directly affects host homeostasis. The gastrointestinal-kidney dialogue gives interesting information about the pathogenesis of multiple kidney diseases. Moreover, aging is followed by specific shifts in the human microbiome, and gradual elimination of physiological functions predisposes to inflammaging, sarcopenia and disease. Aging is characterized by a microbiota with abundance of disease-associated pathobionts. Multiple factors such as immune system, environment, medication, diet, genetic endowment are involved in determining the age microbiome in health and disease. Our present review promotes recent acquired knowledge and is expected to inspire researchers to advanced studies and investigation of the involved pathways of the gut microbiota and kidney axis.